From IWRM back to integrated water resources management - Giordano, Mark; Shah, Tushaar (Informa UK Limited, 2014)
Integrated water resources management provides a set of ideas to help us manage water more holistically. However, these ideas have been formalized over time in what has now become, in capitals, Integrated Water Resources Management (IWRM), with specific prescriptive principles whose implementation is often supported by donor funding and international advocacy. IWRM has now become an end in itself, in some cases undermining functioning water management systems, in others setting back needed water reform agendas, and in yet others becoming a tool to mask other agendas. Critically, the current monopoly of IWRM in global water management discourse is shutting out alternative thinking on pragmatic solutions to existing water problems. This paper explains these issues and uses examples of transboundary water governance in general, groundwater management in India and rural–urban water transfer in China to show that there are (sometimes antithetical) alternatives to IWRM which are being successfully used to solve major water problems. The main message is that we should simply get on with pragmatic politics and solutions to the world’s many individual water challenges.